2007
DOI: 10.1002/jmri.21149
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety concept for multichannel transmit coils

Abstract: Purpose: To propose and illustrate a safety concept for multichannel transmit coils in MRI based on finite-differences time-domain (FDTD) simulations and validated by measurements. Materials and Methods:FDTD simulations of specific absorption rate (SAR) distributions in a cylindrical agarose phantom were carried out for various radio frequency (RF) driving conditions of a four-element coil array. Additionally, maps of transmit amplitude, signal phase, and temperature rise following RF heating were measured by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 21 publications
2
74
0
Order By: Relevance
“…T½ C ¼ 200:2 À 105:9 Á Df gB 0 [7] with B 0 the amplitude of the static field and g the gyromagnetic ratio of hydrogen nuclei in MHz=T. This result is within the range of the other relationships described in literature.To quantify background gradients caused by the susceptibility distribution of the setup, a B 0 map was constructed out of the scans without flyback.…”
Section: Methodssupporting
confidence: 84%
See 1 more Smart Citation
“…T½ C ¼ 200:2 À 105:9 Á Df gB 0 [7] with B 0 the amplitude of the static field and g the gyromagnetic ratio of hydrogen nuclei in MHz=T. This result is within the range of the other relationships described in literature.To quantify background gradients caused by the susceptibility distribution of the setup, a B 0 map was constructed out of the scans without flyback.…”
Section: Methodssupporting
confidence: 84%
“…MRT can also be useful for RF safety assessments in MR (4)(5)(6)(7). Simulation studies have shown that RF deposition quantified by specific absorption rate (SAR) can spatially be very inhomogeneous, leading to hotspots that can exceed temperature limits set in regulations (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…[27]). In a practical implementation, there are various options how to define the channel weights w. One approach is to use the voltages supplied to the RF amplifiers or the RF power at the feeding ports of the RF coil [10]. The multi-channel body coil used in this work is equipped with pick-up coils to monitor the currents in each Tx element [28].…”
Section: Rf Shimmingmentioning
confidence: 99%
“…Instead, local SAR estimates are usually obtained based on numerical simulations of the RF field propagation in human body models. First approaches concentrated on estimates of the worst-case SAR that could occur for any expected input signal [10,11]. However, this restricts the allowed RF duty-cycle significantly, prohibiting even the use of sequences that are allowed with conventional quadrature excitation [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Especially for highly accelerated RF pulses, the specific absorption rate (SAR) tends to increase rapidly and can easily exceed the SAR guidelines (16)(17)(18)(19). On the other hand, when integrated in the RF pulse design, pTx offers additional degrees of freedom to manipulate the SAR deposition for a given target excitation pattern (7).…”
mentioning
confidence: 99%